1999
DOI: 10.1074/jbc.274.31.21963
|View full text |Cite
|
Sign up to set email alerts
|

26 S Proteasome-mediated Production of an Authentic Major Histocompatibility Class I-restricted Epitope from an Intact Protein Substrate

Abstract: Peptides displayed on the cell surface by major histocompatibility class I molecules (MHC class I) are generated by proteolytic processing of protein-antigens in the cytoplasm. Initially, antigens are degraded by the 26 S proteasome, most probably following ubiquitination. However, it is unclear whether this proteolysis results in the generation of MHC class I ligands or if further processing is required. To investigate the role of the 26 S proteasome in antigen presentation, we analyzed the processing of an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 43 publications
1
30
0
1
Order By: Relevance
“…This suggests that the relevant antigen-processing compartment translates multiple mRNAs into DRiPs whose peptides compete for class I binding. Although our findings are limited to VV-derived peptides, it is likely that they extend to peptides derived from cellular proteins, because the findings provide an explanation for CD8 + T cell recognition of peptides encoded by low abundance or unusual mRNAs, as well as for the poor correlation between the immunopeptidome and the transcriptome or proteome (14)(15)(16). Consistent with the proposal that immunoribosomes translate nascent RNA (4), Gu et al (17) recently reported that truncated RNA generated via RNAi are an efficient source of antigenic peptides.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the relevant antigen-processing compartment translates multiple mRNAs into DRiPs whose peptides compete for class I binding. Although our findings are limited to VV-derived peptides, it is likely that they extend to peptides derived from cellular proteins, because the findings provide an explanation for CD8 + T cell recognition of peptides encoded by low abundance or unusual mRNAs, as well as for the poor correlation between the immunopeptidome and the transcriptome or proteome (14)(15)(16). Consistent with the proposal that immunoribosomes translate nascent RNA (4), Gu et al (17) recently reported that truncated RNA generated via RNAi are an efficient source of antigenic peptides.…”
Section: Discussionmentioning
confidence: 99%
“…The GAr module failed to impair ODC degradation or impose partial degradation when inserted in two positions of ODC other than residue 424, and alternative inserts into or near position 424 did not alter degradation (Ref. 34 and results not shown). GFP consists primarily of a tightly folded ␤-barrel (35), and ODC to the N-terminal side of residue 424 consists of a highly structured ␤-sheet domain (36).…”
Section: Discussionmentioning
confidence: 99%
“…To assay effective presentation, we inserted the ovalbumin-derived SIINFEKL epitope in-frame into the backbone of TCR␣. The SIINFEKL epitope was demonstrated previously to be suitable for the study of N-extended epitopes (36,41). Because the target glycosylation consensus sequence is Asn-X-Ser/Thr (where X stands for any amino acid but proline), it is possible to insert the SIINFEKL sequence two residues downstream of the glycosylation site such that its serine residue serves as part of the consensus sequence.…”
Section: The Presence Of a Sugar Moiety Near A Class I Mhc Epitopementioning
confidence: 99%